Quality evaluation of commercial masmin of lakshadweep - Shersha, U. P. (KUFOS, 2014)
Abstract- Masmin is a smoked dried tuna product that is both economically and nutritionally important to the people of Lakshadweep Islands. The objectives of the study were to determine the organoleptic, biochemical and microbial qualities of commercially produced masmin sold in various markets of Minicoy, Agatti and Andrott islands of Lakshadweep.